Beef Cattle Waste Management as an Effort to Reduce Environmental Pollution - Rusman, Rusni Fitri Y.; Mirnawati, Mirnawati; Aldi, M; HM, Zaenal (Pascasarjana Universitas Sulawesi Tenggara, 2022)
Waste management is one solution in utilizing beef feces in a beef cattle business. This study aims to provide an overview of waste management in a beef cattle business in Maros Regency, namely CV Enhal Farm. This research was conducted with a direct visit to the location of the Enhal Farm farm located in Tompobulu Village, Tompobulu District, Maros Regency, South Sulawesi. This research was carried out for a month, starting from April to May 2020. The data collection technique was by making direct observations of activities related to the company's operations in order to obtain information directly. The results of the study show that livestock waste management at CV Enhal Farm is carried out starting from the selection of feed to processing biogas which can produce methane gas.